ANALISIS PENGARUH ECONOMIC VALUE ADDED DAN FAKTOR FUNDAMENTAL PERUSAHAAN LAINNYA TERHADAP RETURN SAHAM DENGAN CORPORATE SOCIAL RESPOSIBILITY SEBAGAI VARIABEL PEMODERASI (Studi Empiris Pada Perusahaan Yang Terdaftar Dalam Indeks Kompas-100 Di BEI Tahun 201 - Putri Renalita Sutra Tanjung (MIX: JURNAL ILMIAH MANAJEMEN, 2014)
Abstract: This research aim to analyze influence of EVA (Economic Value Added), DER (Debt to Equity Ratio), ROE (Return on Equity), and PER (Price to Earning Ratio), to Return of Share with Corporate Social Responsibility as a moderating variable.Technique sampling is purposive sampling. The research is conducted on 42 companies, which consistently include in the Kompas-100 Index in Indonesia Stock Exchange with 3 (three) years (2010-2012) range of time. The estimation model beingused is panel data regression, with Fixed Effect Method approach.Simultaneously, all variables have positive effect and significantto return of share. The estimation results in partial indicate that EVA havepositive effect but do not significant to return of share. DER, ROE, PER and CSR having significantly positive effect to return of share.Corporate Social Responsibility is significantly as a moderating variable of the relationship between EVA, DER, ROE, and PER to return of share.Keywords: EVA, DER, ROE, PER, CSR, Return of Share